2022
DOI: 10.1021/acs.inorgchem.2c00420
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry, Local Molybdenum Clustering, and Electrochemistry in the Li2+xMo1–xO3 Solid Solutions

Abstract: A broad range of cationic nonstoichiometry has been demonstrated for the Li-rich layered rock-salt-type oxide Li 2 MoO 3 , which has generally been considered as a phase with a well-defined chemical composition. Li 2+x Mo 1−x O 3 (−0.037 ≤ x ≤ 0.124) solid solutions were synthesized via hydrogen reduction of Li 2 MoO 4 in the temperature range of 650−1100 °C, with x decreasing with the increase of the reduction temperature. The solid solutions adopt a monoclinically distorted O3-type layered average structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…At the same current density, the discharge capacity of the LMO sample after 100 cycles was only 76.5 mA h g −1 , and the capacity retention rate was only 30.5%. According to previous literature, [13][14][15][16][17][18]25,47,48 it is found that the cycling performance of pristine LMO is actually rather poor, and the reasons for this phenomenon are very complex. For Li-rich cathode materials, the irreversible phase transformation/structural rearrangement, the dissolution of the TM ions into the electrolyte, and the surface side reactions were proposed to be…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…At the same current density, the discharge capacity of the LMO sample after 100 cycles was only 76.5 mA h g −1 , and the capacity retention rate was only 30.5%. According to previous literature, [13][14][15][16][17][18]25,47,48 it is found that the cycling performance of pristine LMO is actually rather poor, and the reasons for this phenomenon are very complex. For Li-rich cathode materials, the irreversible phase transformation/structural rearrangement, the dissolution of the TM ions into the electrolyte, and the surface side reactions were proposed to be…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…Even though various experimental analyses evidenced ordered arrangements of Mo and Li in Li 2 MoO 3 , the exact ordering is still unknown. ,, Therefore, Savina et al argued that the α-NaFeO 2 structural type for Li 2 MoO 3 is an oversimplified model. They have observed a quasi-ordered Mo 3 O 13 cluster arrangement and symmetry lowering to a monoclinic structure with a C 2/ m space group . Moreover, in recent work by Kim et al, the C 2/ m phase of Li 2 MoO 3 is identified as a nearly stable structure with a slight energy difference from the rhombohedral structure with space group R 3̅ m …”
Section: Introductionmentioning
confidence: 96%
“…The Li 2 MoO 3 has an α-NaFeO 2 type structure with an R3̅ m space group, while others have a honeycomb interlayer Li/M ordering in their ground state. 12,13 Multiple studies discuss the disordered nature of Li 2 Mo 0.90 Co 0.10 O 3 , 25 etc. The study by Ma et al 10 has proved that Li 2 MoO 3 is an attractive replacement for Li 2 MnO 3 to use as a cathode in LIBs.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations